Student Responses to Hydrostatic Pressure Physics Learning Using the Phet Simulation-Based Inquiry Method - Lola Salsabila; Fauzan Sulman; Aminah Zb (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The purpose of this study was to determine students' responses to learning about hydrostatic pressure using the PhET Simulation-based inquiry method. Simulation-based learning was chosen because the material on hydrostatic pressure is abstract and requires visualization to improve conceptual understanding. Understanding the concept is a process for someone to think in order to be able to understand and understand a concept in learning and also to process a learning material that will be received so that it becomes more (Fitriyani et al., 2023). The research was conducted at MAN 2 Kota Jambi with 15 students from class XI F8 selected using purposive sampling. The research approach used a quantitative approach with a descriptive method. The research instrument was a 1–5 Likert scale questionnaire consisting of 10 statements, covering two main aspects: (1) attitude towards the PhET Simulation media, and (2) general attitude towards learning. Data were collected after students participated in inquiry-based learning that allowed them to explore the variables of depth, density, and gravity through independent simulation.The descriptive analysis results show that the overall average score was 4.12, which falls into the